Evaluation of groundwater level, quality and recharge: a case study of Can Tho City, Viet Nam - Van Ty, Tran; Trung Tri Dang, Trinh; Dinh Giang Nam, Nguyen; Vuong Thu Minh, Huynh (Vietnam Journal of Science and Technology, 2023)
This study evaluated the groundwater levels (GWLs) and groundwater quality of Can Tho city (CTC) using statistical analysis and a Groundwater Quality Index (GWQI). In addition, the groundwater recharge potential from rainfall was investigated for the period 2001-2009. The results show that GWLs decreased rapidly in the period 2000-2010 and gradually in the period 2012-2018 in both the Middle-upper Pleistocene (qp2-3) and Upper Pleistocene (qp3) aquifers. This is due to excessive withdrawals, especially to meet the demands of production facilities in the city’s industrial zones. In this regard, Decree No. 2946/UBND-KT of the People’s Committee of CTC was issued and enacted in 2012, which resulted in a marked reduction in withdrawals and contributed to GWL stabilization. Groundwater quality in CTC was found to be mainly affected by coliform in both dry and wet seasons. However, groundwater quality improved during the wet season with the dilution of rainfall, as shown by the GWQI values. In addition to groundwater recharge from rainfall, other socio-economic factors such as urbanization, industrialization, and the influence of the Bassac River on recharge potentials should be further investigated.